Akibat Hukum Ketidaklengkapan Penjabaran Audit dalam Pengadaan Barang/Jasa Pemerintah Berdasarkan Peraturan Presiden Nomor 12 Tahun 2021 - Rahmawati, Anisa Pasha; Negara, Tunggul Anshari Setia (Universitas Negeri Malang, 2022)
This study aimed to analyze the types of audits in government goods/services procurement under Presidential Regulation Number 12 of 2021 and the legal consequences of the incomplete descriptions of audits in government goods/services procurement. The type of research used in this study was normative juridical with a statute approach, a concept approach, and a case approach. Data collection was done by using library research techniques. The data obtained were analyzed using law interpretation techniques. The results of the study showed that Presidential Regulation Number 12 of 2021 concerning Amendments to Presidential Regulation Number 16 of 2018 concerning Procurement of Goods/Services did not explain in detail the main tasks and functions of the Government Internal Supervisory Apparatus in carrying out audits of government procurement of goods/services. The legal consequences of incomplete audit rules in the procurement of government goods/services gave rise to multiple interpretations, so it was necessary to establish an internal regulation or a Regent's regulation related to the main tasks and functions of the Government's Internal Supervisory Apparatus.